Atividade antiofídica induzida pelo extrato hidroalcoólico de ocotea notata. - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Snakebite accidents affect millions of people around the world every year, especially in tropical regions, and in April 2009 the World Health Organization included them on the list of neglected tropical diseases. The use of medicinal plants for the treatment of diseases or against the effect of poisons in accidents with scorpions, bees, wasps, and especially snakes, has been shown as complementary or alternative therapy to conventional therapies for a long time. The mechanisms of interaction between plant extracts with antifungal characteristics and the components that are responsible for the severe effects of poisoning such as phospholipases A2, proteases, hemorrhages, hyalorunidases, proteases, cytotoxins, mycotoxins and neurotoxins are not clear. deeper. The delay in treatment is a factor that aggravates the situation in this type of accident increasing the severity and the neurological damage both peripheral and central. Thus, the search for biocomplexes and biotive substances in plants related to antiophidic and neuroprotective characteristics is shown as a perspective for reducing the severity of these accidents and a possible form of joint therapy that already exists in cases of poisoning. In view of this, the present study observed the neuroprotective and antiophidic potential of the hydroalcoholic extract of Ocotea notata in both the central and peripheral nervous systems and evaluated a possible mechanism of pharmacological action on injuries caused by the venom of Crotalus durissus terrificus to Brazilian rattlesnake. Determining the specificity of chemical interactions between poison toxins and bioactive plant components is the key point for the development of phytocomplexes that exhibit true pharmacological efficacy and less loss of their therapeutic potential. For the study of the neuroprotective and antiophidic characteristics of Ocotea notata extract, the techniques of hippocampal slices of mouse, MTT assay and chick biventer cervicis electromyography, with n = 5 samples for each condition. With these experiments it was observed that Ocotea notata extract does not induce central and peripheral neurotoxicity in mammal and bird nervous system and that it induces neuroprotection against Crotalus durissus terrificus venom. It was also seen that its efficiency in counteracting the neurotoxic effects of crotalic venom may be associated with the presence of flavonoids in the extract, thus, these results reinforce the biotechnological potential of the extract as an antineurotoxic agent of natural origin.
Keywords: Terapia alternativa; Envenenamento; Ocotea nonata; Crotalus durissus terrificus; CNPQ::CIENCIAS BIOLOGICAS